Three-dimensional development of the palate in bilateral orofacial cleft newborns 1 year after early neonatal cheiloplasty: Classic and geometric morphometric evaluation - Jaklová, Lenka; Borský, Jiří; Jurovčík, Michal; Hoffmannová, Eva; Černý, Miloš; Dupej, Ján; Velemínská, Jana (Journal of cranio-maxillo-facial surgery, 2020)
OBJECTIVES: The aim of this study was to assess palatal growth in newborns with complete bilateral cleft lip and palate (cBCLP) and bilateral cleft lip and palate with tissue bridges (BCLP + B) 1 year after early neonatal cheiloplasty (ENC). MATERIAL AND METHODS: The methodology was based on classic and morphometric analysis of dental models of newborns with cBCLP or BCLP + B. These analyses included metric analysis, coherent point drift-dense correspondence analysis, superprojection methods, and multivariate statistics. Dental casts were observed in two age categories, which were compared with each other. The first cast was obtained from each patient before ENC (T0, 5 ± 5 days) and the second one prior to palatoplasty (T1, 12 ± 6 months). RESULTS: Fifty-two dental models obtained from 26 newborns with cBCLP and BCLP + B were evaluated. The results showed that over the 12-month period, alveolar clefts were narrowed in both cleft types due to anterior growth combined with the formative effect of suturing. This was confirmed by decreases in the dimensions of the right (T0 9.93 ± 2.80 mm, T1 6.64 ± 2.43 mm; p ≤ 0.003) and left (T0 10.71 ± 4.13 mm, T1 6.69 ± 4.29 mm; p ≤ 0.003) alveolar clefts in cBCLP patients. Similar reductions in alveolar cleft widths occurred on the left side (T0 11.69 ± 4.75 mm, T1 4.34 ± 2.97 mm; p ≤ 0.001) of BCLP + B patients, while on the right side, which was connected by a combined tissue bridge, there was non-significant narrowing of the alveolar cleft (T0 1.61 ± 1.34 mm, T1 1.04 ± 0.70 mm; p = 0.120). The ENC did not restrict posterior palatal growth, meaning that intertuberosity width was extended in cBCLP (T0 32.80 ± 3.15 mm, T1 35.86 ± 2.80 mm; p ≤ 0.001) and in BCLP + B neonates (T0 34.01 ± 2.15 mm, T1 36.21 ± 2.14 mm; p ≤ 0.004). Width and length measurements in the observed groups showed growth tendencies equivalent to those in noncleft or LOP patients. Palatal variability was greater in neonatal cBCLP, but was reduced during the monitored period, approximating that for BCLP + B. Regions with the most notable palatal growth were located primarily at the premaxilla and at the anterior and partially posterior ends of the maxillary segments. CONCLUSION: Early neonatal cheiloplasty had no negative effect on palatal growth in any direction. There was no reduction in the length or width of the palate during the first year of life, nor was there narrowing of the dentoalveolar arch. The formative effect of the operated lip on the anterior part of the palate was confirmed. This, in combination with the favorable growth, lead to closure of the alveolar cleft.
Keywords: maxila; rozštěp rtu; Cleft Palate; Dental Arch; Geometric morphometry; kojenec; Dental arch; rozštěp patra; Cleft Lip; Infant; Models, Dental; zubní oblouk; Palate development; zubní modely; Infant, Newborn; novorozenec; Humans; Classic morphometry; Bilateral cleft lip and palate; Neonatal cheiloplasty; lidé; Maxilla